Physical Properties Investigations of Natural Rubber Composites Using Cetyltrimethylammonium Bromide (CTAB) as Modifier of Local Clay Filler - Hasan, Abu; Junaidi, Robert; Yerizam, Muhammad; Arifin, Fatahul (Department of Chemical Engineering, Universitas Gadjah Mada, 2023)
Improved absorption of rubber backbone on filler surfaces is necessary to enhance the physical properties of rubber vulcanizate. One of the ways to repair the surface of the filler is through modifying using surfactant. Hence, this study aims to compare the physical properties of natural rubber vulcanizates using clay filler and modified clay with cetyltrimethylammonium bromide (CTAB). The processes that were followed to achieve the objectives of this research were the design of rubber formulas, mastication and milling of rubber, and testing of the physical properties of rubber vulcanization. The clay characterization and its modification using FTIR and XRD were also carried out. Characterization using FTIR and XRD showed that there was indeed a clay modification with CTAB. Natural rubber compounds were also analyzed using SEM. The torque on the rheometer for modified clay with CTAB is 12.34 kg-cm higher than for original clay, which is 7.05 kg-cm. Elongation at break and tensile strength for vulcanizate using CTAB-modified clay filler is lower than that using original clay, with 300% modulus and hardness increase. Thus, clay modification using CTAB as a filler has a good effect on the curing characteristics and physical properties of natural rubber vulcanization compared to only using local clay as a filler.